Konsep Kewarganegaraan Ganda dalam Tinjauan Hukum Positif dan Hukum Islam - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Irfan Ammar Najib; Khanafi Rizki Pratama; Yuliana Fajar Nur Hidayati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research discusses the concept of dual citizenship in the perspective of Indonesian positive law and Islamic law. Dual citizenship refers to the legal status in which a person is recognized as a citizen by more than one country, a phenomenon that is increasingly relevant in the era of globalization. In Indonesian positive law, dual citizenship is generally not recognized, except in special cases such as children from mixed marriages. However, increasing global mobility and individual rights have prompted discussion on the need for wider recognition of dual citizenship. Meanwhile, Islamic law provides a more flexible approach by considering the maqasid al-shariah principle which emphasizes the protection of basic human rights. Through a normative juridical and sociological approach, this research explores how the two legal systems deal with dual citizenship and what the implications are for individuals as well as the state. A comparative study of dual citizenship Dual Citizenship, Positive Law, Islamic Law, Maqasid al-Shariah, Citizenship Regulation practices in several other countries, such as the United States, Canada, Egypt and Pakistan, was also conducted to gain greater insight and understand the best practices that can be adapted in Indonesia. The results show that despite resistance to dual citizenship, its implementation can provide significant benefits, both in terms of protecting individual rights and strengthening international relations. Therefore, it is recommended that Indonesia consider a more comprehensive and inclusive policy regarding dual citizenship, which is in line with positive legal values and Islamic legal principles. This research can hopefully serve as a reference for policy makers and academics in developing regulations that are adaptive to global dynamics.